2019
DOI: 10.1038/s41586-019-1422-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signatures of many-body correlations in magic-angle twisted bilayer graphene

Abstract: The discovery of superconducting and insulating states in magic angle twisted bilayer graphene (MATBG) 1,2 has ignited considerable interest in understanding the nature of electronic interactions in this chemically pristine material system. The phenomenological similarity of the MATBG transport properties as a functionof doping with those of the high-Tc cuprates and other unconventional superconductors 1,2,3 suggests the possibility that MATBG may be a highly interacting system. However, there have not been an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

58
503
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 668 publications
(590 citation statements)
references
References 29 publications
58
503
5
3
Order By: Relevance
“…(where = is the full bandwidth -from valence band bottom to conduction band top), in rough agreement with the values deduced from STM [16][17][18][19] and compressibility 34 experiments. Of course, we do not expect the free-electron picture to apply at low temperatures, since there interactions change the physics dramatically.…”
Section: Measurementssupporting
confidence: 83%
See 1 more Smart Citation
“…(where = is the full bandwidth -from valence band bottom to conduction band top), in rough agreement with the values deduced from STM [16][17][18][19] and compressibility 34 experiments. Of course, we do not expect the free-electron picture to apply at low temperatures, since there interactions change the physics dramatically.…”
Section: Measurementssupporting
confidence: 83%
“…This system shows a host of electronic phases, including correlated insulators 3,9,10 , Chern insulators [11][12][13] , superconductors 4,9,10 , and ferromagnets 14,15 . Scanning tunneling spectroscopy [16][17][18][19] and electronic compressibility measurements 20,21 indicate that in this system Coulomb interactions and kinetic energies are indeed comparable. In this regime, there is an inherent tension between localized and itinerant descriptions of the physics.…”
mentioning
confidence: 76%
“…Stacking two graphene layers with a controlled interlayer twist angle (θ ) elegantly solves this problem because the two rotated Dirac cones hybridize and form a new superlattice vHs with an energy that decreases as θ is reduced, [2][3][4][5][6] leading to tunable correlation effects such as unconventional superconductivity as well as charge and spin ordering effects. [7,8] This level of tunability not only makes such correlated physics accessible to electron-transport [9][10][11][12][13][14] and -tunneling experiments, [15][16][17][18] but also leads to the possibility of tuning the vHs resonantly with a desired optical excitation. [19] Optical conductivity measurements have shown that wide tunability of θ is especially promising for controlling lightinduced coherent interactions between excited carriers in the vHs of twisted bilayer graphene (twBLG).…”
Section: Doi: 101002/adma202001656mentioning
confidence: 99%
“…In addition, flat valley Chern bands can be realized in tBLG with aligned hBN substrate [41][42][43], twisted double bilayer graphene [44][45][46], ABC trilayer graphene on hBN [47][48][49] and twisted bilayer transition metal dichalcogenides [50,51], etc. The small bandwidths make electron-electron interactions important [52][53][54][55][56][57][58][59], and further lead to intriguing interacting phases in experiments including superconductivity, correlated insulator and QAH effect.So far, all of the experimental Moiré systems are timereversal (TR) invariant at the single particle level, thus the total Chern number always equals to zero. Therefore, even with flat bands, it is difficult to achieve TR breaking interacting topological states such as the FCI in these systems.…”
mentioning
confidence: 99%